ANALISIS PENYEBAB KANDASNYA MV. TANJUNG MANIS SAAT MEMASUKI ALUR PELAYARAN SEMPIT SUNGAI MAHAKAM - Nur Ardianty Razak; Makmur; Rajuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Grounding incidents in narrow waterways remain one of the major causes of navigational accidents that affect the safety and efficiency of ship operations. The Mahakam River is one of Indonesia's busiest inland waterways, characterized by narrow channels, sedimentation, tidal influences, and high traffic density, which increase navigational risks. This study aims to analyze the factors causing the grounding of MV. Tanjung Manis while entering the narrow navigation channel of the Mahakam River. The research employed a qualitative descriptive approach using a case study method. Data were collected through onboard observation, interviews with the master, chief officer, second officer, and helmsman, as well as documentation of navigational activities. The findings reveal that the grounding was caused by the interaction of three major factors. Human error included inadequate bridge communication, suboptimal Bridge Resource Management (BRM), reduced situational awareness, and inappropriate decision-making during a meeting situation with another vessel. Internal factors involved the limited performance of the echo sounder in detecting accurate under keel clearance due to heavy sedimentation. External factors consisted of narrow and shallow channels, sediment accumulation, tidal conditions, and dense vessel traffic in the Mahakam River. The study concludes that grounding prevention requires effective bridge team communication, proper utilization of navigational equipment, compliance with COLREG Rule 9 regarding narrow channels, and continuous situational awareness throughout navigation.